2017
DOI: 10.37341/jkg.v2i1.33
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Dukungan Keluarga Dengan Tingkat Kecemasan Pada Pasien Gagal Ginjal Kronis Yang Menjalani Hemodialisis DI RSUD Dr. Soehadi Prijonegoro Sragen

Abstract: Family Support, Level Of Anxiety, Chronic Renal Failure, And Hemodialysis. Chronic kidney disease is a threat for human because the prevalency increase every years. Patient of chronic kidney disease with teraphy hemodialysis can cause psychological pressure pasca hemodialysis. One example of psychological pressure is anxiety. For decrease anxiety of patient with terapy hemodialysis need family support. Objectives To identity the relationship among family support with level of anxiety chronic renal failure of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
2
1
0
1
Order By: Relevance
“…The surrounding environmental conditions such as family support and assistance also affect the level of anxiety. This is similar to the research conducted by Ika, et al 14 who stated that there was a significant relationship between family support and anxiety levels with powerful strength. Although respondents who have severe stage can experience mild and moderate anxiety due to the influence of the duration of treatment and the surrounding environment.…”
Section: Discussionsupporting
confidence: 90%
“…The surrounding environmental conditions such as family support and assistance also affect the level of anxiety. This is similar to the research conducted by Ika, et al 14 who stated that there was a significant relationship between family support and anxiety levels with powerful strength. Although respondents who have severe stage can experience mild and moderate anxiety due to the influence of the duration of treatment and the surrounding environment.…”
Section: Discussionsupporting
confidence: 90%
“…Providing education can effectively increase the patient's ability to manage their disease [15]. The previous study found that education can increase knowledge and change attitudes but do not change negative perceptions about the disease so that at times it can worsen the patient's condition [16]. This study was in line with the results of Ariyanti's research that self-efficacy training can prevent the progression of kidney damage [6].…”
Section: Discussionsupporting
confidence: 80%
“…Pada kondisinya di populasi, penelitian Al Aziz dan Sudiro di Sragen mendukung teori tersebut yaitu adanya hubungan dukungan keluarga dengan tingkat kecemasan dengan kekuatan yang sangat kuat yaitu semakin tinggi dukungan keluarga semakin tidak ada kecemasannya. 17 Dan dalam penelitian yang dilakukan oleh Effendi di Palembang bahwa ada hubungan antara dukungan emosional, dukungan penghargaan, dukungan informatif, dukungan instrumental dengan tingkat kecemasan. 18…”
Section: Dukungan Keluarga Dengan Tingkat Kecemasanunclassified